Association of Oscillatory Ventilation during Cardiopulmonary Test to Clinical and Functional Variables of Chronic Heart Failure Patients - Reis,Hugo Valverde (2018)
Abstract Objective: The aim of this study is to characterize the presence of exercise oscillatory ventilation (EOV) and to relate it with other cardiopulmonary exercise test (CET) responses and clinical variables. Methods: Forty-six male patients (age: 53.1±13.6 years old; left ventricular ejection fraction [LVEF]: 30±8%) with heart failure were recruited to perform a maximal CET and to correlate the CET responses with clinical variables. The EOV was obtained according to Leite et al. criteria and VE/VCO2 > 34 and peak VO2 < 14 ml/kg/min were used to assess patients' severity. Results: The EOV was observed in 16 of 24 patients who performed the CET, as well as VE/VCO2 > 34 and peak VO2 < 14 ml/kg/min in 14 and 10 patients, respectively. There was no difference in clinical and CET variables of the patients who presented EOV in CET when compared to non-EOV patients. Also, there was no difference in CET and clinical variables when comparing patients who presented EOV and had a VE/VCO2 slope > 34 to patients who just had one of these responses either. Conclusion: The present study showed that there was an incidence of patients with EOV and lower peak VO2 and higher VE/VCO2 slope values, but they showed no difference on other prognostic variables. As well, there was no influence of the presence of EOV on other parameters of CET in this population, suggesting that this variable may be an independent marker of worst prognosis in HF patients.